2013
DOI: 10.1108/jfc-05-2013-0040
|View full text |Cite
|
Sign up to set email alerts
|

Detection and prevention of financial abuse against elders

Abstract: (2015),"Finance-seeking behaviour and outcomes for small-and medium-sized enterprises", International Journal of Managerial Finance, Vol. 11 Iss 4 pp. 513-530 https://doi.org/10.1108/IJMF-01-2013-0005 Access to this document was granted through an Emerald subscription provided by All users group For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This study has demonstrated that a suspicion of financial abuse perpetrated towards older people is not uncommon among bank managers' experiences; all participants had multiple examples of case suspicions. Similar to the literature on financial abuse of older people (Gilhooly et al, 2013;Harries et al, 2014;Dalley et al, 2017), the case accounts reflected many types of financial abuse, both related to family members and opportunism (rogue traders, lottery scams). A systematic review and meta-analysis (Burnes et al, 2017) identified that a minimum of one in 18 older people living the community are subject to scams every year.…”
Section: Cases Involving Issues Related To Capacitymentioning
confidence: 82%
“…This study has demonstrated that a suspicion of financial abuse perpetrated towards older people is not uncommon among bank managers' experiences; all participants had multiple examples of case suspicions. Similar to the literature on financial abuse of older people (Gilhooly et al, 2013;Harries et al, 2014;Dalley et al, 2017), the case accounts reflected many types of financial abuse, both related to family members and opportunism (rogue traders, lottery scams). A systematic review and meta-analysis (Burnes et al, 2017) identified that a minimum of one in 18 older people living the community are subject to scams every year.…”
Section: Cases Involving Issues Related To Capacitymentioning
confidence: 82%
“…The authors have no relevant nancial or non-nancial interests to disclose. Financial** Includes theft, fraud, exploitation, pressure in connection with wills, property, inheritance or nancial transactions, or the misuse or misappropriation of property, possessions or bene ts [39] *Also known as 'emotional' abuse **Only vulnerable adults can be nancially abused as, unlike children, they have assets [40] Table 2. Variables identi ed and their variation for the vignettes developed 1 Emergency Department Pharmacist Practitioner Acute Medical Unit…”
Section: Fundingmentioning
confidence: 99%
“…The prominence of EA due to isolation, abandonment and social exclusion cannot be denied (Heuser and Howe, 2019; Ojagbemi et al , 2013). The deprivation of finance, status, respect, choices and decisions are observed evidence of EA (Patel and Mishra, 2018; Trainor, 2015; Harries et al , 2014; Dong et al , 2014). The violation of elders’ human, legal and medical rights are gravest social ill due to a variety of reasons such as modernization, less social integration (SI), caregiver stress (CGS), etc (Malek and Razzak, 2017; Maschi et al , 2014; Bhattacharya and Bhattacharya, 2014).…”
Section: Introductionmentioning
confidence: 99%